Collagenous Colitis: Histologic Progression, Extraintestinal Features and Lack of Response to 5-ASA - A Case Report - Franzjosef Schweiger (Canadian Journal of Gastroenterology)
Collagenous colitis is a clinicopathologic syndrome which presents as chronic, watery, nonbloody diarrhea. Colonic biopsies characteristically show a thick subepithelial collagen band. Barium enema and colonoscopy generally fail to establish the diagnosis. This case report provides evidence for histologic progression over time, pancolonic involvement and the presence of extraintestinal features of collagenous colitis. The reported patient showed no response to 5-aminosalicylic acid. Colonoscopic biopsies in cases of chronic diarrhea can save the patient repeated, uncomfortable and costly investigations.